Educational Leadership in Latin Europe: A European Perspective - Moos, Lejf (Journal of Educational, Cultural and Psychological Studies (ECPS Journal), 2015)
Much of the contemporary literature and theory of leadership has, as its starting point, the image of governance and public school leadership, an image that is very close to the vision proposed by the OECD. This view is strongly influenced by the way the neo-liberal Anglo-American approach analyzes and outlines the political and administrative characteristics of school organization. However, you cannot apply the same practices and policies all over the world, such as in the countries of Latin America. This general introduction is put forward with a framework in which we can reflect their own situation. It cannot be realistic to have a «one size fits all» policy such as the method of governance the OECD implies. An important addition to the traditional Anglo-American perspective presented in these pages is the discussion on the fact that strong leadership from above can be replaced by a perspective of distributed leadership, inserting the concepts of leadership within social contexts and a broader policy.
Keywords: Agenzie transnazionali; Contesto sociale; Distribution; Distribuzione; Governance; Leadership; OCSE; OECD; Societal context; Transnational agencies